Popular Egyptian cinema : gender, class, and nation - Shafik, Viola, 1961- (Cairo, Egypt ; New York : American University in Cairo Press, 2007)
Viola Shafik examines popular and commercial movies from Egypt's film industry, including a number of the biggest box-office hits widely distributed in Egypt and the Arab world. She examines these films against the backdrop of the country's overall socio-political development, from the emergence of the film industry in the 1930s, through the Nasser and Sadat eras, up to the era of globalization.
Part I. Nation. The other ; The allegorical nation -- Part II. Gender. Feminism and femininity ; Female stardom, myth production, and morality -- Part III. Class. Negotiating class through genre ; Audiences and class.
Online resource; title from PDF title page (EBSCO, viewed October 23, 2017).
Includes bibliographical references (pages 327-338) and indexes.
eBooks on EBSCOhost
Keywords: Motion pictures -- Social aspects -- Egypt -- History; Motion pictures -- Egypt -- History; Sex role in motion pictures; Social classes in motion pictures; National characteristics in motion pictures; Cinéma -- Aspect social -- Égypte -- Histoire; Cinéma -- Égypte -- Histoire; Rôle selon le sexe au cinéma.; Classes sociales au cinéma.; Caractéristiques nationales au cinéma.; PERFORMING ARTS -- Reference; PERFORMING ARTS -- Film & Video -- Reference; Motion pictures -- Social aspects; Motion pictures; National characteristics in motion pictures; Sex role in motion pictures; Social classes in motion pictures; Egypt; Film; Ägypten; Massenkultur; History